Mitochondria in Early Life - He, Ling; Maheshwari, Akhil (Current Pediatric Reviews, 2023)
Mitochondria are highly-dynamic, membrane-bound organelles that generate most of the chemical energy needed to power the biochemical reactions in eukaryotic cells. These organelles also communicate with the nucleus and other cellular structures to help maintain somatic homeostasis, allow cellular adaptation to stress, and help maintain the developmental trajectory. Mitochondria also perform numerous other functions to support metabolic, energetic, and epigenetic regulation in our cells. There is increasing information on various disorders caused by defects in intrinsic mitochondrial or supporting nuclear genes, on different organ systems. In this review, we have summarized the ultrastructural morphology, structural components, our current understanding of the evolution, biogenesis, dynamics, function, clinical manifestations of mitochondrial dysfunction, and future possibilities. The implications of deficits in mitochondrial dynamics and signaling for embryo viability and offspring health are also explored. We present information from our own clinical and laboratory research in conjunction with information collected from an extensive search in the databases PubMed, EMBASE, and Scopus.
Keywords: Neonate